1996
DOI: 10.1038/381042a0
|View full text |Cite
|
Sign up to set email alerts
|

Structure and mutational analysis of Rab GDP-dissociation inhibitor

Abstract: The crystal structure of the bovine alpha-isoform of Rab GDP-dissociation inhibitor (GDI), which functions in vesicle-membrane transport to recycle and regulate Rab GTPases, has been determined to a resolution of 1.81 A. GDI is constructed of two main structural units, a large complex multisheet domain I and a smaller alpha-helical domain II. The structural organization of domain I is surprisingly closely related to FAD-containing monooxygenases and oxidases. Sequence-conserved regions common to GDI and the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
204
2

Year Published

1996
1996
2004
2004

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(219 citation statements)
references
References 47 publications
13
204
2
Order By: Relevance
“…We have previously determined the crystal structure of bovine a-GDI involved in recognition of Rab3 GTPases that regulate neurotransmitter release in the synapse (6,7) at 1.81 A , resolution (8). We found that a-GDI is constructed of two main structural units, a large multi-sheet domain I containing residues from both the N-and C-terminus of the protein, and a smaller entirely a-helical domain II insert (residues 119-219) found at the base of a-GDI.…”
mentioning
confidence: 99%
“…We have previously determined the crystal structure of bovine a-GDI involved in recognition of Rab3 GTPases that regulate neurotransmitter release in the synapse (6,7) at 1.81 A , resolution (8). We found that a-GDI is constructed of two main structural units, a large multi-sheet domain I containing residues from both the N-and C-terminus of the protein, and a smaller entirely a-helical domain II insert (residues 119-219) found at the base of a-GDI.…”
mentioning
confidence: 99%
“…Many if not all small GTPases of the Ypt/Rab family within an organism can be regulated by the same Ypt/Rab-GDI. First insights into the specificity of GDI-Rab interaction have been reported [4,35], but detailed mechanisms remain to be determined. Rab-gdi genes have been cloned from animal and yeast cells so far.…”
Section: Discussionmentioning
confidence: 99%
“…Algal GDIVlp is nearly equally similar to mammalian, insect, worm, and fungal Rab-GDI, but a rice EST-derived sequence shares greater similarity with GDIVlp than with the remaining sequences (Table 1). Interestingly, GDIVlp shows unique deviations within three 'sequence-conserved regions' (SCRs), which have recently been defined as the best conserved structural and functional RabfYpt-GDI cores [4]. Two of the deviations are conservative (Leu-Ile in SCR1A, Gly-Ala in SCR3B), but one introduces an additional positive charge (Gly-Lys in SCR1 B; Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations